A rare nonsense variant of the X-gene in a paediatric patient with severe peripheral pulmonary stenosis. (14th October 2021) - Chida-Nagai, A; Sawai, S; Yakuwa, S; Akagawa, H; Furutani, Y; Takakuwa, E; Takeda, A
Abstract: Background: Most cases of peripheral pulmonary stenosis (PPS) associated with William's syndrome are usually very mild or resolve spontaneously. However, we encountered a paediatric case of William's syndrome (WS) with severe PPS. In this case, we investigate whether the patient's genetic background was responsible for the severity of the PPS. Case presentation: Shortly after birth, the male patient was suspected as WS because of his peculiar facial appearance and PPS. Fluorescence in situ hybridization identified microdeletion in the 7q11.23 region, and he had a confirmed diagnosis of WS. PPS became worsened subsequently, and a cardiac catheterization was performed at the age of 7 years. Due to severe multiple PPS, the right ventricular pressure exceeded the left ventricular pressure. At the age of 12, he had haemoptysis, which required ventilatory management. A pseudoaneurysm of the right pulmonary artery was identified and a right middle lobectomy was performed. Methods and results: First, we performed multiplex ligation-dependent probe amplification and whole exome sequencing, considering the possibility of homozygous mutations in the region responsible for WS (7q11.23) or a larger deletion of this region in the patient. The deletion was confirmed to be a heterozygous deletion with a typical range for WS. Therefore, we hypothesized that the causative gene of severe PPS may exist separately from the region responsible for WS. After reviewing the result of the whole exome sequencing, we identified a rare nonsense variant of the "X"-gene as the disease-causing gene. The X-gene is involved in the suppression of vascular smooth muscle cell proliferation and the generation of pulmonary arteriolar dilator "Y". The X-gene has been reported as a disease-causing gene in patients with pulmonary arterial hypertension. Based on these previous reports, we assumed that the X gene variant could be a cause of PPS; therefore, we performed functional analysis. We first introduced a mutant X-gene construct into human pulmonary arterial endothelial cells (hPAECs) and human pulmonary arterial smooth muscle cells and found that the mutant significantly reduced the production of Y compared to the wild-type X-gene. When transfected into hPAECs, the mutant X gene significantly increased cell proliferation compared to the wild-type X-gene. The hPAECs also showed reduced caspase 3/7 activity and reduced apoptosis compared to wild-type X-gene transfected cells. In the patient's own lung pathology specimens, irregular fibrous thickening of the intima of the intrapulmonary arteries was observed, which supported the results of the functional analysis. Conclusion: Our study showed that an X-gene variant could lead to reduced Y production in the pulmonary arteries, abnormal proliferation of hPAECs, and the development of severe PPS. As Y-replenishing drugs are already in clinical use, the results may lead to the development of medical treatments for severe PPS. Funding Acknowledgement: Type of funding sources: None.